2010
DOI: 10.1088/0004-637x/712/1/692
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Kinematics of the Stellar Halos and Thick Disks of the Milky Way Based on Calibration Stars From Sloan Digital Sky Survey Dr7

Abstract: The structure and kinematics of the recognized stellar components of the Milky Way are explored, based on well-determined atmospheric parameters and kinematic quantities for 32360 "calibration stars" from the Sloan Digital Sky Survey (SDSS) and its first extension, (SDSS-II), which included the sub-survey SEGUE: Sloan Extension for Galactic Understanding and Exploration. Full space motions for a sub-sample of 16920 stars, exploring a local volume within 4 kpc of the Sun, are used to derive velocity ellipsoids … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

103
703
20
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 482 publications
(829 citation statements)
references
References 124 publications
103
703
20
3
Order By: Relevance
“…In addition, a second peak around −2.1 is observed. This is very close to the median metallicity value associated with the outer-halo region (Carollo et al 2010;Allende Prieto et al 2014;FA15).…”
Section: [X/h] Vs Rsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, a second peak around −2.1 is observed. This is very close to the median metallicity value associated with the outer-halo region (Carollo et al 2010;Allende Prieto et al 2014;FA15).…”
Section: [X/h] Vs Rsupporting
confidence: 78%
“…The derived MDF from [M/H] also shows a second peak at [M/H] ∼ −2.1, which resembles the median metallicity value associated with the outer-halo population (Carollo et al 2007(Carollo et al , 2010Beers et al 2012).…”
Section: Discussionmentioning
confidence: 65%
“…The break in the stellar density profile could also be an indication that the Milky Way has a "dual stellar halo," containing populations of different origins (Carollo et al 2007(Carollo et al , 2010Beers et al 2012). Simulations predict that the stellar halo is composed both of accreted stars and stars that form in situ (e.g., Zolotov et al 2009;Font et al 2011;McCarthy et al 2012;Tissera et al 2012;Cooper et al 2015).…”
Section: Dual Stellar Halo: In Situ Star Formationmentioning
confidence: 99%
“…Hartwick (1987) showed that the metal-poor RR Lyrae stars delineate a two-component halo, with a flattened inner component and a spherical outer component. Carollo et al (2010) identified a two-component halo and the thick disk in a sample of 17,000 SDSS stars, mostly with [Fe/H] < −0.5. They described the kinematics well with these three components:…”
Section: The Galactic Stellar Halomentioning
confidence: 99%